TERMITE FAUNA OF KRAKATAU AND ASSOCIATED ISLANDS, SUNDA STRAITS, INDONESIA - M. L. Thakur; R. K. Thakur (BRIN Publishing (Penerbit BRIN), 1992)
Frequent volcanic eruptions, submergence and emergence of some of theIndonesian islands has made them ail object of intense biogeographical significance. These geological catastrophies resulted in complete sterilization of the area biologically, wiping out all forms of life. Subsequent reuegetation and establishment of new fauna attracted many scientists, some of them having made very significant contributions. The present contribution deals with termite fauna of Krakatau and associated islands. In all, twenty five species and 13 genera, the highest number so far reported, from Carita (9 species), Panaitan Islands (6 species), Rahota Besar (2 species), Anak Krakatau and Sertung (1 species each) have been recorded in this publication. Of these, while, Prorhinotermes panaitanensis is new to science, two species (Glyptotermes besarensis and G. panaitanensis) have been described recently by the senior author (MLT). Similarly Glyptotermes minutus, Nasutitermes culasiensis and Hospitalitermes buzpnensis have been recorded for the first time from the Indonesia. Several other species are new distributional records. Nasutitermes matagensis matagensiformisand Schedorhinotermes javanicus are the most successfully colonizedspecies, recorded almost in all the islands under reference. Besides the taxonomic treatment of the fauna, the paper also gives key to genera based on soldier caste.